Challenges of Waste Growth through Collaborative City Governance in Batam City - Sari, Cindy Fatika; Salsabila, Lubna; Lodan, Karol Teovani; Dompak, Timbul (Dialogue : Jurnal Ilmu Administrasi Publik, 2024)
This abstract examines the challenges of waste growth in Batam City through the lens of collaborative city governance. It underscores the critical need for joint efforts among government, industry, and society to address the escalating issue of solid waste. The analysis highlights existing initiatives and the obstacles faced in implementing effective waste management practices, particularly the fragmented nature of current collaborations and persistent community behaviors that hinder progress. Key challenges identified include low environmental awareness, limited community participation in waste sorting, inadequate infrastructure, and inconsistent enforcement of regulations. The abstract emphasizes the necessity for intensified education, awareness-building, and incentivization to enhance community engagement. Proposed solutions include strengthening regulatory frameworks, improving coordination among government agencies, and increasing corporate responsibility towards sustainability. These measures aim to create a comprehensive waste management system that enhances environmental quality and supports sustainable economic development in Batam City. By addressing these challenges through collaborative governance, Batam City can achieve a cleaner, healthier environment and sustainable growth for its residents